Study the campus weather observation for environmental monitoring - Abu Eusuf, Muhammad; Jahn Kassim, Puteri Shireen; Mohd Latiff, Nur Hanie (2008)
A Micro-scale modeling system is being applied on an experimental basis at the International Islamic University Gombak campus for production of real/-time, high resolution weather forecasts. The numerical experiment is being supported by IIUM. It is believed to be the first time that a real-time microclimate data has been monitored by the department of BTE- KAED routinely similar with other Malaysian university, although this data will transfer for meso-scale models to run in real local time in IIUM- KAED laboratories. The forecast cycle is initiated automatically by the Department of Building Technology and Engineering's AWS. The data- set constructed on the grid system is then transmitted by a software info-Gap when all data have been received, quality checked, and preserved. These forecasts can be performed routinely on a daily basis, or they can be initiated when large-scale numerical guidance from the AWS indicates the possible development of significant disturbances. Regular inspection of the weather forecasts is serving as a medium for further improvements in the numerical model and is stimulating the development of techniques for evaluation of forecast skill and/or utilization of this guidance in an operational setting. The main focus of this paper is to discuss about the data acquisition of climate control parameters and their effective utilization in microclimate research and development.